Nanoparticles, a promising treatment for gastric cancer - Di Hua; Xiexing Wu; Zebin Wu; Chunyang Fan; Jiale Wang; Wei He; Yongkang Deng; Yao Zhang; Hengxiang Shu; Meng Shen; Dechun Geng; Kai Chen (Smart Materials in Medicine)
Globally, gastric cancer (GC), as a fatal malignant tumor, remains a significant health challenge. Thus, it is imperative to explore novel treatment strategies. Despite the fact that the survival rate of GC has improved over the past few decades, the median survival for patients with advanced GC is still less than one year. Recently, nanoparticles (NPs), as a potential approach for designing new treatment strategies, such as gold NPs (AuNPs) and metal oxides NPs (MONPs), not only possesses advantages such as multi-functional imaging and high stability, but also can deliver drugs, simultaneously achieve diagnostic and therapeutic effects. With the development and maturation of this technology, an increasing number of nano-drugs have been utilized in the diagnosis and treatment of GC. In this review, we have provided a detailed and separate elaboration on the NPs that play diagnostic, therapeutic and dual-functional roles in GC-related research. We also introduce the clinical research of nanomedicine in GC over the past few decades. Furthermore, we probed into the limitations of contemporary nanomedicine treatments and the future research directions.